A Lightweight Workbench for Database Benchmarking, Experimentation, and Implementation - Xinyuan Zhao; Gadia, S. K. (IEEE transactions on knowledge and data engineering, 2012)
We have developed a platform, called Cyclone Database Implementation Workbench (CyDIW), that can be used to implement new database prototypes, use existing command-based systems, and conduct experiments. The workbench allows seamless integration of multiple systems and provides useful services. To support database implementation page-based storage and buffer managers are built-in. A scripting language for batches of commands is included. Experiments are encapsulated as batches of commands on multiple systems. A simple and easy to use GUI is available that acts as an editor and a launchpad for execution of batches of commands. Emphasis in CyDIW is on simplifying the logistics surrounding setting up experiments that are comprehensive and self-contained. The benchmarking services in CyDIW can be used for lightweight benchmarking, where a benchmark consisting of a data set and a suite of commands is given. A benchmarking experiment collects performance statistics from multiple systems based on varying parameters and plots benchmarking results without leaving the GUI. Setup for the system is easy. All configuration settings are recorded in XML documents that are highly portable and readily visible. Once installed, batches representing experiments can be exchanged as text files and executed on CyDIW on any computer.